Revealed Preferences for Utilitarian Cycling Energy Expenditure versus Travel Time - Elmira Berjisian; Alexander Bigazzi (Findings)
This paper quantifies the perceived cost of utilitarian cycling energy expenditure as the marginal rate of substitution between energy expenditure and travel time (MRS~et~). This trade-off manifests in, and can be inferred from cyclist cruising speeds. Median MRS~et~ values for observed cruising events in a naturalistic cycling dataset range from 0.05 to 0.95 min/km per kcal/min. The revealed cost of energy expenditure (relative to travel time) increases significantly with road grade, traffic controls, and certain facility types, and is also significantly higher for women, less-dedicated cyclists, and people riding on weekends and for non-commute purposes.